Gestão escolar e conselho de escola, que relação é esta? Um estudo em busca de novas formas de cooperação entre escola-comunidade na Região de Sorocaba – SP - Dulcinéia de Fátima Ferreira; Kelen Christina Leite; Maria Carla Corrochano (EccoS – Revista Científica)
This study is the result of the research project: School management and school council: what is this relationship? An analysis of community participation experiences from school councils in Sorocaba – SP, Brazil. As a starting point, it could be identified the relationship between school and community from the school councils. The main goals of this research were to map community involvement experiences at school from the school counciland to analyze and reveal the power of this collective experience. It is a qualitative research focused on cartographic approach. As a result, various mobilizing devices are pointed, as well as the potential for new forms of school- community cooperation. This research was supported by MCTI/CNPq/MEC/Capes and is bound to the research group Community Education and Social Movements UFSCar –Sorocabacampus.